PENGGUNAAN TWO STAY TWO STRAY DAN NUMBERED HEADS TOGETHER DALAM PEMBELAJARAN SEJARAH - Tila Paulina; Maskun Maskun; Yustina Sri Ekwandari (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2014)
This study aims to determine students’ cognitive achievement on learning history subject at 11th grade of Social class uses a combination of two stay two stray (TSTS) and numbered heads together (NHT) model in SMA Muhammadiyah 2 Bandar Lampung. The design of study was The One-Shot Case Study. The population was all 11th grade student of Social class in SMA Muhammadiyah 2 Bandar Lampung on academic year 2013/2014, totally 94 students. The samples were taken by using random sampling technique. Based on the research, it is concluded that the combination use of two stay two stray (TSTS) and numbered heads together (NHT) model in SMA Muhammadiyah 2 Lampung as follow: students’ cognitive achievement at the highest cognitive level is knowledge (CI) 70 the category (Good), and the category of the highest cognitive learning achievement is scored 70-79 (Good) 43.75 %.Tujuan penelitian ini adalah mengetahui hasil belajar kognitif siswa dalam pembelajaran sejarah kelas XI IPS menggunakan model kombinasi Two Stay Two Stray (TSTS) dan Numbered Heads Together (NHT) di SMA Muhammadiyah 2 Bandar Lampung. Desain penelitian adalah The One-Shot Case Study. Populasi penelitian adalah seluruh siswa kelas XI IPSSMA Muhammadiyah 2 Bandar Lampung yang berjumlah 94 orang. Sampel diambil dengan menggunakan teknik random sampling. Berdasarkan penelitian disimpulkan bahwa penggunaan model kombinasi Two Stay Two Stray (TSTS) dan Numbered Heads Together (NHT) di SMA Muhammadiyah 2 Bandar Lampung sebagai berikut: hasil belajar kognitif siswa pada jenjang kognitif tertinggi adalah Pengetahuan (CI) 70 kategori baik  dan kategori hasil belajar kognitif siswa tertinggi adalah nilai 70-79 (Baik) 43,75%.Kata kunci : hasil belajar, model two stay two stray, numbered heads together